النظام القبلي في اليمن ومكوناته وموقف الشريعة اللإسلامية منه: The Tribal System in Yemen And the Position of Islamic Law on It - Usman, Muhammad Abduh; Amer Abdulwahab Mahyoub Murshed; Mohamad Zaidi bin Abdul Rahman (Journal Al-Muqaddimah, 2020)
This study touched upon the nature of the tribe and its meaning and the concept of the tribal system, especially the tribal system of Yemen, with the components of this system, its sources, and the legitimate position of it. The study showed that the tribal system is based on the nervousness of the family, in this system, and then be other manifestations of this system, such as the characteristics and characteristics that must be Sheikh, and how to elect, and so on. Tribal custom is a constitution or method and approach under which the tribes in resolving disputes or disputes, which represents a law governing the tribal social fabric, and from sources Islamic law and customs and judgment’s experience and jurisprudence and the experience of the judge, and it became clear that the tribe and its system in the curriculum of Islam does not good or bad itself, but on the basis of how to employ and how much the impact on the community for building of the fabric and strengthen its immunity.